Mathematics Attitude of Future Teachers of Stem Subjects - Jančařík, Antonín; Marcom, Guilherme; Kleinke, Maurício (Journal of Education Culture and Society, 2023)
Aim. This paper presents research aimed at testing the mathematical self-efficacy of mathematics and computer science student teachers. The aim of the presented phase of the research was to verify the effectiveness of the chosen research instrument after translation into Czech, its applicability within the specific environment of the preparation of future teachers and the design of a shorter version of the questionnaire.Methods. 97 students of the first and second year of Bachelor's degree studies at the Faculty of Education of Charles University, specialising in mathematics and computer science, were interviewed either in a single-subject form or in combination with a second subject. Subsequently, the data was processed and evaluated using quantitative methods.Results. The results confirmed that the test, even when translated into Czech, fully met the claim of high reliability (Cronbach's Alpha = 0.965). Using the Principal Axis Factoring method with Varimax with Kaiser Normalisation in 11 iterations, convergence to the four basic components, which were characterised as Motivation and Enjoyment, Anxiety, Self-confidence and Value, was achieved.Conclusion. The research has shown that the chosen research instrument, the ATMI questionnaire, is fully functional after translation into English and use in the environment of preparation of future mathematics and science teachers. The first measurement data also confirms that attitudes towards mathematics are very different among future mathematics and science teachers. It also confirmed the assumption that the questionnaire has the potential to identify students who have problematic attitudes towards mathematics and are therefore at risk of dropping out.